2015
DOI: 10.4314/tjpr.v14i10.28
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Pharmacology of Isatin and its Derivatives: A Review

Abstract: Isatin (1H-indole-2,3-dione), an indole derivative of plant origin, is involved in many pharmacological activities like antiallergic, antimalarial, antiviral and antimicrobial; isatin and its derivatives have been found to show promising results against various cancer cell lines. Isatin is a versatile precursor for many biologically active molecules and its diversified nature makes it a versatile substrate for further modifications. This review provides a brief overview on the recent advances and future perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 40 publications
0
32
0
3
Order By: Relevance
“…Naturally occurring (figure 1) and synthetic OXs have also been found to display a diverse array of biological properties, including antimalarial, antifungal, anticonvulsant, anti-HIV, radical scavenging and antibacterial activities and anti-cancer activities [23][24][25][26][27][28][29]. Their anti-cancer activity is attributed to a number of mechanisms such as inhibition of caspase [30,31], p53 induction [32] and inhibition of the tumour suppressor gene p53 [33].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring (figure 1) and synthetic OXs have also been found to display a diverse array of biological properties, including antimalarial, antifungal, anticonvulsant, anti-HIV, radical scavenging and antibacterial activities and anti-cancer activities [23][24][25][26][27][28][29]. Their anti-cancer activity is attributed to a number of mechanisms such as inhibition of caspase [30,31], p53 induction [32] and inhibition of the tumour suppressor gene p53 [33].…”
Section: Introductionmentioning
confidence: 99%
“…Isatin is an important heterocyclic system because of its inimitable role in medicinal chemistry. Numerous alkaloids, drugs, dyes, pesticides and analytical reagents contain this structural motif in their core structure . A large number of isatin derivatives have been reported in literature exhibiting a wide spectrum of biological activities that include anticancer, antibacterial, antiviral, anticonvulsant, anti‐inflammatory, antifungal activity, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous alkaloids, drugs, dyes, pesticides and analytical reagents contain this structural motif in their core structure. [13,14] A large number of isatin derivatives have been reported in literature exhibiting a wide spectrum of biological activities that include anticancer, [15] antibacterial, [16] antiviral, [17] anticonvulsant, [18] antiinflammatory, [19] antifungal activity, [20] etc. Isatin derivatives (compound 1-4, Figure 1b) have also been explored for their α-glucosidase inhibitory potential and the results obtained were encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits endogamous activity in mammals (Chaudhary et al, 2013) and has shown cardioinhibitory effects on a frog's heart, and hypotensive, respiratory depression and antidiuretic effects (Pandeya et al, 2005). Isatin also possess anticancer (Khan et al, 2015), antioxidant (Sammaiah & Pragathi, 2014), antiviral (Gomathi et al, 2013), antimicrobial (Saxena et al, 2015), analgesic (Pal et al,201), anti-inflammatory (Hajare & Chinchole, 2013), antitubercular (Aboul-fadl & BinJubair, 2010), anticonvulsant (Raj, 2012) and antianxiety (Grewal, 2014) activities.…”
Section: Structure Descriptionmentioning
confidence: 99%